2017
DOI: 10.1177/2292550317728038
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and Complications of Improved Liposuction–Curettage Through Mini-Incisions for the Treatment of Axillary Osmidrosis

Abstract: These data suggest that LC with a final phase of improvement through mini-incisions is effective for AB treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…Hu et al . describe a surgical technique that involves making mini-incisions in the axilla and using liposuction-curettage to remove the apocrine glands [ 12 ]. A study involving 449 axillae found that patients who underwent well-organised liposuction-curettage and received appropriate post-operative care experienced excellent elimination of malodor in 89.81% of cases.…”
Section: Discussionmentioning
confidence: 99%
“…Hu et al . describe a surgical technique that involves making mini-incisions in the axilla and using liposuction-curettage to remove the apocrine glands [ 12 ]. A study involving 449 axillae found that patients who underwent well-organised liposuction-curettage and received appropriate post-operative care experienced excellent elimination of malodor in 89.81% of cases.…”
Section: Discussionmentioning
confidence: 99%
“…23 Many surgeons have modified the liposuction technique to decrease the high recurrence rate of osmidrosis, including suction pressure, cannula size, aperture number, and aperture edge sharpness. 13,24,25 Recurrence after liposuction is highly associated with the tools and methods used. The whole procedure of liposuction is difficult to standardize.…”
Section: Ta B L E 3 Operation Areas and Timesmentioning
confidence: 99%
“…The main characteristic of axillary bromhidrosis is an excessive foul odour in the axillary region due to the interaction of secretions from the apocrine glands with microorganisms. 1 The treatment methods include nonsurgical approaches, such as the use of topical antiperspirants, the injection of botulinum toxin A, 2 ethanol injection, 3 antibiotic administration, the use of fragrances, and surgical methods, such as laser surgery, 4 surgical epilation, 5 and liposuction curettage. 1 Among these approaches, the surgical methods are more effective and have longer lasting results than the nonsurgical methods.…”
Section: Introductionmentioning
confidence: 99%
“…1 The treatment methods include nonsurgical approaches, such as the use of topical antiperspirants, the injection of botulinum toxin A, 2 ethanol injection, 3 antibiotic administration, the use of fragrances, and surgical methods, such as laser surgery, 4 surgical epilation, 5 and liposuction curettage. 1 Among these approaches, the surgical methods are more effective and have longer lasting results than the nonsurgical methods. 6 However, surgical methods, according to some reports, can also be accompanied by complications such as hematoma, scars, and necrosis.…”
Section: Introductionmentioning
confidence: 99%